A Pilot Study Exploring Obesity-Related Differences in Fall Rate and Kinematic Response Resulting From a Laboratory-Induced Trip. Issue 4 (1st October 2016) - Garman, Christina R.; Nussbaum, Maury A.; Franck, Christopher T.; Madigan, Michael L.
Abstract : OCCUPATIONAL APPLICATIONS A higher percentage of young adults with a higher body mass index (BMI) fell after a laboratory-induced trip compared to young adults with a lower BMI, although this difference did not reach statistical significance. Young adults with a higher BMI also exhibited a kinematic response to the trip that was less favorable than adults with a lower BMI. This study provides preliminary evidence that obesity may increase the risk of falls after tripping among young obese workers, and that this increased risk may be due to a less favorable balance recovery response after tripping. Additional larger scale studies are needed to better understand contributing and modifiable factors that can be targeted via intervention or other fall prevention strategies. TECHNICAL ABSTRACT Background : Obese adults are reported to fall at a higher rate than non-obese adults. Purpose : To help determine the reason for this higher fall rate, we quantified fall rates, kinematics at trip onset, and kinematics during the response to a laboratory-induced trip among two groups of young adults with higher and lower body mass indexes (BMI) that approximated obese and healthy-weight ranges. Our focus was on young adults given that they comprise a substantial portion of the workforce. Methods : Twenty-one young adult subjects, including 10 with a lower BMI (19.4–25.7 kg/m 2 ) and 11 with a higher BMI (29.8–42.9 kg/m 2 ), walked along a 10 m walkway at a purposeful speed. During a randomly selected walking trial, an obstacle was raised to elicit a trip. Results : Among the 19 subjects who unambiguously fell or recovered, 30% of subjects with higher BMI fell and 0% of lower BMI subjects fell, but this difference did not reach statistical significance. Among the 15 subjects who used an elevating strategy, all recovered balance, and the only kinematic response variable that differed between BMI groups was that recovery step time was longer among the higher BMI group. Among the four subjects who used a lowering strategy, no statistical analysis was possible due to a small number of subjects, but several measures were consistent with a less favorable kinematic response among the three higher BMI fallers compared to the one lower BMI subject who recovered. Conclusions : This study provides preliminary evidence that obesity may adversely influence fall rate and recovery kinematics after tripping among young adults. Additional larger scale studies are needed to better understand contributing and modifiable factors that can be targeted via intervention.